Asian Yearbook of International Law, Volume 8 (1998-1999) - Chimni, B.S; Swan, Sik Ko; Miyoshi, Masahiro; Pinto, M.C.W; Subedi, Surya (Brill | Nijhoff, 2003)
The Asian Yearbook of International Law is a major refereed publication dedicated to international law issues as seen primarily from an Asian perspective. This is the first publication of its kind edited by a team of leading international law scholars from across Asia. The Asian Yearbook of International Law provides a forum for the publication of articles in the field of international law, and other Asian international law topics, written by experts from the region and elsewhere. Its aim is twofold: to promote international law in Asia, and to provide an intellectual platform for the discussion and dissemination of Asian views and practices on contemporary international legal issues. As a rule, each volume of the Asian Yearbook normally contains articles; notes; a section on State practice; an overview of the participation of Asian countries in multilateral treaties; a chronicle of events and incidents; surveys of the activities of international organizations which have special relevance to Asia, such as a survey of the activities of the Asian-African Legal Consultative Committee; and book review, bibliography and documents sections.
Keywords: International law -- Asia -- Periodicals.; International law; Asia; Periodicals